17. yüzyılda yapılmış mensur Şehnâme tercümesi (I. vr. 553a-573b) (inceleme - metin - dizin) - Cav, Seval (My University, 2010)
Eser, İstanbul Üniversitesi Merkez kütüphanesi 6131 demirbaş numarasıyla kayıtlıdır. Üç cilt halinde ve tamamı 1778 varaktır. Ayrıca eserde minyatürlere yer verilmiş, her sayfası 25 satır olarak düzenlenmiştir. Üzerinde çalışılan 1. cildin boyu 39, eni 24.5, kalınlığı 7.5 cm'dir. Eser Hicrî 1187, Milâdî 1773 yılında tamamlanmıştır. Kelime kelime bir tercüme değildir. Tez yazmanın 553a-573b varaklarını kapsamaktadır. Bu tezi hazırlamaktaki amaç Şehname'nin bu mensur tercümesini tanıtmaktır. Bu çalışma giriş, metin ve sözlük olmak üzere üç bölümden oluşmaktadır. Giriş kısmında Firdevsî, Şehname, Şehname çevirileri ve üzerinde çalışılan yazmayla ilgili bilgiler verilmektedir. Metin kısmında sayfa ve satır numaraları belirtilmiş, günümüz noktalama işaretlerine göre düzenlenmiş ve gerekli kısımlarda paragraflar yapılmıştır. Böylece eserden faydalanılması daha kolay hale getirilmek istenmiştir. Sözlük bölümünde eserin söz varlığını gösteren bir indeks hazırlanmış; eserdeki kelime ve birleşik şekillerin metindeki anlamları verilmeye çalışılmıştır.

The book is registered under fixture number 6131 at the Central Library of İstanbul Universty. It is composed of 3 volumes with total pages of 1778. Also miniatures have taken place in the book with each page designed in 25 lines. The length of the first volume on which the book is being carried on, is 39 cm, the width is 24.5 cm and thickness 7.5 cm. The book was completed in 1187 -date based on Hegira, in 1173 —date based on Chiristian Era; it is not a translation word by word. The thesis includes the pages 553a-573b of the manuscript. The aim in preparing this thesis is to introduce the translation of Şehname as a prose. This work is composed of three sections which are the introduction, the text and the dictionary. in the introduction part, information about Firdevsi, Şehname, Şehname translations and the manuscript on which the work is carried on; is given. In the text, the page and line nubbers are shown, designed according to today's punctuation marks and in necessary parts paragraphs are created. in this way, it has been aimed to get benefit of the work more easily. In dictionary, an indexs is prepared which shows the vocabulary of the book; the meanings of the words and compound forms in the book are tried to be explained.
Keywords: Türk Dili